Готельне господарство країн Азії та Близького Сходу: сучасний стан та перспективи розвитку - Сологуб, Юрій Іванович; Безпала, Ольга Василівна; Харченко, Олена Миколаївна (My University, 2025)
Стаття присвячена аналізу сучасного стану та подальших шляхів розвитку готельного господарства країн Азії та Близького Сходу. Готелі країн Азії та Близького Сходу цілком вписуються в глобальну туристичну систему. У готелях представлених регіонів сервіс і комфорт орієнтований в першу чергу на західного туриста. Ряд засобів розміщення все ще зберігають в тій чи іншій мірі свої національні особливості. Такі готельні підприємства все частіше стають музеями, або переходять в категорію засобів розміщення екстра класу. Спираючись на значну кількість проєктів готельних підприємств, що знаходяться на стадії розробки та тенденцію до зростання розміру ринку та заповнюваності, перспективи готельної індустрії Азії та Близького Сходу в найближчі роки – це зростання. За останнє десятиліття готельна індустрія в країнах Азії та Близького Сходу постійно зростала в розмірах і доходах. Індустрія пропонує широкий вибір варіантів розміщення, від бюджетних готелів до розкішних курортів. The article is devoted to the analysis of the current state and further development paths of the hotel industry in Asia and the Middle East. Hotels in Asia and the Middle East fit perfectly into the global tourism system. In the hotels of the presented regions, service and comfort are primarily focused on Western tourists. A number of accommodation facilities still retain their national characteristics to one degree or another. Such hotel enterprises are increasingly becoming museums or moving into the category of extra-class accommodation facilities. Based on the significant number of hotel enterprise projects under development and the trend towards an increase in market size and occupancy, the prospects for the hotel industry in Asia and the Middle East in the coming years are growth. Over the past decade, the hotel industry in Asia and the Middle East has been constantly growing in size and revenue. The industry offers a wide range of accommodation options, from budget hotels to luxury resorts. In addition to revenues, the globalization of regional hotels has also had a positive impact on establishing a positive consumer reputation in the global accommodation market, which significantly strengthens the region's position in terms of the development of the tourism sector as a whole. The hospitality industry is one of the first industries to open up to foreign investment in the region. In particular, due to the growing interest in outbound tourism in China, Chinese hotels have rapidly expanded to popular holiday destinations such as Southeast Asia and Europe. Along with the prevalence of smart devices and digital payments, the online hotel booking business in China, Japan, and the UAE has flourished in the past decade. The online short-term rental business is also gaining momentum. Compared with traditional hotel services, short-term rentals offer guests more flexibility and the opportunity to interact with locals. UAE, China, Japan - hotels in these countries are in roughly equal demand among both business travelers and ordinary tourists. Turkey, Thailand, Malaysia, Indonesia are more likely to be beach holiday regions.
Keywords: готельне господарство; розвиток туристичної сфери; development of tourism; hotel industry; hotel industry